Electrophysiological analysis of retrieval of conditioned taste aversion in rats. Unit activity changes in critical brain regions - Buresová, O; Aleksanyan, Z A; Bures, J (Physiologia Bohemoslovaca, 1979)
Gustatory discrimination testing shows that rats with an overtrained conditioned taste aversion (CTA) to isotonic LiCl stop salt intake after 1 to 2 licks at the LiCl spout and move to the adjacent water spout within 0.7 s. Activity of 526 neurones from the nucleus of the solitary tract, gustatory thalamus, gustatory cortex, lateral and ventromedial thalamus, and amygdala was recorded in naive or CTA trained rats during the above gustatory discrimination. Post-stimulus histograms (PSH) triggered by water or salt licks or by spout switching were plotted for single units. Population responses of various regions were obtained by integration of the statistically significant excitatory and inhibitory intervals in the individual PSHs. Lick related changes of unit activity were orserved in 52% and 65% of neurones in control and CTA trained rats, respectively. The CTA training increased the incidence of units in which salt licking influenced the activity less than water licking. Presentation of the aversive fluid induced inhibition of unit activity in the gustatory cortex, ventromedial hypothalamus, and amygdala and excitation in the lateral hypothalamus. The changes started 100 to 150 ms after spout switching and culminated 100 ms later. Activity of the solitary tract nucleus and gustatory thalamus was affected less consistently. The results indicate that the gustatory cortex, amygdala and hypothalamus participate in CTA retrieval but a more specific identification of the electrical correlates of memory readout and of drinking control was not possible.
Keywords: Animals; Sodium Chloride; chloridy; lithium; Action Potentials; Electrophysiology; chlorid sodný; Avoidance Learning; Lithium; Medulla Oblongata; Thalamus; chuť; mozek; Conditioning, Classical; Hypothalamus; Male; klasické podmiňování; amygdala; Brain; učení vyhýbat se; hypothalamus; thalamus; Amygdala; krysa rodu Rattus; Taste; elektrofyziologie; mozková kůra; Cerebral Cortex; akční potenciály; zvířata; mužské pohlaví; Chlorides; Rats; medulla oblongata